INFLUENCE OF TITANIUM INTERLAYER THICKNESS ON THE ADHESION OF TiCN THIN FILMS DEPOSITED ON STAINLESS STEEL - Brown, Austin (My University, 2017)
Hard coatings deposited by physical vapour deposition (PVD) are commonly used to improve the scratch resistance and hardness of objects made of softer materials such as steel, and they can also be used as decorative coatings since they exhibit a wide range of different colours. In this research, stainless steel tableware utensils were coated with multilayer Ti/TiCN thin films to give the tableware a wear-resistant decorative finish. A cathodic arc PVD system was used to deposit the coatings since it has the potential to produce very dense coatings with excellent adhesion and wear-resistance properties in relatively short deposition times. Several system parameters were varied between deposition cycles to create a large set of samples which included: changing the amount of flatware present inside of the chamber during deposition, changing the size of the flatware used, changing the mounting location of the flatware inside of the chamber, and changing the depletion level of the titanium cathode targets used to deposit titanium. It was found that changing these variables had an effect on the deposition rate of the coating and thus had an effect on the thickness of the titanium interlayer, which was found to be an important factor in achieving good adhesion of the TiCN layer. The optimal titanium interlayer thickness was found to be in the range of approximately 120 to 230 nm.
Keywords: TiCN; Titanium Carbo-Nitride; Interlayer; Adhesion; Deposition; Cathodic Arc PVD